Motivasi Sangat Dibutuhkan Dalam Meningkatkan Kinerja Pegawai (Studi Pada Perumda Air Minum Tirta Moedal Kota Semarang) - Firman Ardiansyah; Sih Darmi Astuti; Raden Ayu Aminah Rizkia Puspita; Tito Aditya Perdana (Lembaga Pengembangan Kinerja Dosen, 2026)
Leadership approaches play an important role in shaping employee development and their work outcomes. On the other hand, high standards of professionalism and the ability to adapt to technological advancements have become key organizational priorities. Equally crucial is the encouragement of work motivation, which can foster enthusiasm and enhance productivity. Belief in motivational values forms the foundation of employees’ work behavior, ultimately driving improvements in performance. This study was conducted to examine the effects of authoritarian leadership style, the level of employee professionalism, and work motivation on employee performance at Perumda Air Minum Tirta Moedal, Semarang City. The research population comprised all employees of Perumda Air Minum Tirta Moedal (259 individuals), with a sample of 70 respondents determined using the Slovin formula. This quantitative study employed SPSS 25 to analyze multiple linear regression. The study found that motivation is the most powerful factor in improving employee performance, followed by employee professionalism. Furthermore, it was found that an authoritarian leadership style had no effect on employee performance